RELATIVE DEVELOPMENT OF PRODUCTIVITY TRAITS DURING THE BREEDING OF DURUM WHEAT - P. N. Mal’chikov; M. G. Myasnikova (Вавиловский журнал генетики и селекции)
We present data illustrating the improvement of durum wheat yield depending on the stage of breeding within 100 years. The relative importance of characteristic features of the production process, ear productivity, coenotical properties, and morphophysiological traits in the process of the genetic improvement of adaptability and yield of durum wheat are considered. Significant roles of spike productivity, culm length, grain proportion in the above-ground biomass, and harvest index at final breeding steps are demonstrated.